Earnings management of brazilian firms in the IFRS era: The role of economic and institutional factors - Viana, D. B. C., Jr..; Lourenço, I. (Contaduría y Administración, 2022)
This study investigates whether accounting quality – more specifically regarding the level of earnings management by accruals – is associated with a country’s economic and institutional factors that change over time in IFRS era. Based on a sample of 1,387 Brazilian firm-year observations and data regarding 2011 to 2018, econometric models are estimated considering the absolute amount of discretionary accruals as proxy for earnings management and different aspects related to economic and institutional factors of preeminent importance to an emerging economy. We show that in general, high inflation, stock market volatility, and policy uncertainty rates, as well as lower regulatory quality, on average, are associated with a higher level of earnings management in Brazil. This study contributes to the accounting literature in emerging economies discussing the role of economic and institutional factors on accounting quality in the IFRS era in one of the largest developing country in the world. Compared to developed countries or even to other developing economies, Brazil stands out as an emerging economy of considerable economic and political instability, making it a valuable setting for this analysis